Prevalence and Risk Factors of Burnout Syndrome Among Preclinical Medical Students at Yarsi University - Arneta Rizqia Latief (PT Publikasiku Academic Solution, 2026)
Burnout syndrome is characterised by chronic physical, emotional, and mental exhaustion caused by prolonged academic stress, manifested in emotional fatigue, cynicism, and decreased academic efficacy. This study aims to analyse the prevalence and risk factors of burnout syndrome among preclinical medical students at Universitas YARSI. The study employed a quantitative analytical observational design with a cross-sectional approach. The population consisted of medical students from cohorts 2023–2025, with a purposive sample of 277 respondents. Data were collected through online questionnaires using the Maslach Burnout Inventory-Student Survey (MBI-SS), School Burnout Inventory (SBI), and BMS-10 to measure burnout levels, alongside internal and external risk factor questionnaires. Data analysis included univariate and bivariate techniques to assess prevalence and the relationships between variables. The results indicated a moderate to high prevalence of burnout among preclinical medical students, with dominant risk factors including academic workload, time management, self-efficacy, and social support. These findings highlight the importance of burnout prevention strategies through resilience enhancement, stress management, and institutional support. This study contributes to the understanding of burnout dynamics in medical education within an Islamic values context and provides a basis for mental health interventions for students.